Pemetaan Rantai Nilai Pada Pengembangan Kawasan Argowisata Gunung Mas - Rike Penta Sitio (Universitas YARSI, 2018)
The development of Gunung Mas Agrotourism is inseparable from other business links along the value chain of Tourism. The tourism value chain approach that supports small people is a way of thinking that tries to shift the mindset of a project that curbs the market into a mindset that has a significant impact on the market. Research on the impact of agro-tourism development of Gunung Mas from economic, social and cultural impacts is based on community perceptions and determines the impact of agro-tourism development seen from the level of income and prosperity. The results of this community perception will be used as part of an alternative development strategy in a sustainable region. The results show that the pattern of global control chain shape that occurs in Gunung Mas agro tourism in its value chain has five segments that allow the local community to contribute in tourism. The five segments are transportation, accommodation, food and entertainment, shopping events, and tourist guides. Maximum empowerment of the five segments will help local people to improve their income. The highest positive impact felt by surrounding communities involved in tourism is the increase in local tax revenues. It is shown from the high score of 199. As for the people who do not take advantage of the economic impact of tourism, the most important is the increasing number of public facilities in Tugu Selatan with a score of 203. The highest socio-cultural Impact for people who are actively involved in tourism is awareness to improve education by 171. While people who are not involved in tourism judge that the most negative impact they feel is the rampant prostitution in their area. The highest value for a positive environmental impact is Gunung Mas's agro-tourism which helps preserve the environment with a score of 199 and the negative impact is traffic congestion for both communities.